2002
DOI: 10.1046/j.1365-8711.2002.05753.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of the broad Hα wing in symbiotic stars

Abstract: In many symbiotic stars there appear broad wings around Hα, of which the formation mechanisms proposed thus far include a fast outflow, motion of the inner accretion disc, electron scattering and Raman scattering of Lyβ. We adopt a Monte Carlo technique to simulate the Raman scattering of ultraviolet photons that are converted into optical photons around Hα, forming broad wings, and compute its polarization. Noting that many symbiotic stars exhibit a bipolar nebular morphology and polarization flip in the red‐… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…Raman scattering of Lyβ wing photons may produce highly polarized Hα emission in a radiative cascade of the form (e.g. Lee & Yun 1998; Yoo, Bak & Lee 2002). This mechanism requires the presence of large H i column densities N H i ≳ 10 20 cm −2 , and has been observed to operate around symbiotic stars (Ikeda et al 2004), and potentially in close proximity to quasars (Lee & Yun 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman scattering of Lyβ wing photons may produce highly polarized Hα emission in a radiative cascade of the form (e.g. Lee & Yun 1998; Yoo, Bak & Lee 2002). This mechanism requires the presence of large H i column densities N H i ≳ 10 20 cm −2 , and has been observed to operate around symbiotic stars (Ikeda et al 2004), and potentially in close proximity to quasars (Lee & Yun 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, polarized Hα lines produced by this mechanism are typically broad (FWHM ∼20–40 Å) and symmetric, with wings extending into both the longer and the shorter wavelengths (see e.g. Yoo et al 2002, their figs 4–8); these features clearly distinguish them from Lyα line emitters.…”
Section: Discussionmentioning
confidence: 99%
“…As is shown by Yoo, Bak & Lee (2002), in the case of Raman scattered Hα wings, the linear degree of polarization is lower in the vicinity of the centre than in the far wing part. This is because the Raman scattering optical depth is smaller in the far wing part and therefore the far wing photons suffer fewer scatterings than those photons near the line centre.…”
Section: Observational Ramificationsmentioning
confidence: 69%
“…The redshifting of the polarization profiles from the peaks of the intensity profiles may be due to a dilution effect from a component of the H emission nebula around the binary system, and/or a depolarization effect by multiple-scattering in an optically thick H i nebula. The depolarization in the center of the line was suggested by Yoo, Bak, & Lee (2002), who concluded that the degree of polarization tends to be higher through the wing than around the center. This is because the cross section of Raman scattering steeply increases with proximity to the center of Ly in wavelength and the opacity becomes thick at the line center.…”
Section: Discussionmentioning
confidence: 93%
“…The ratio ðLyÞ=ðO viÞ is $3000 at the velocity of maximum polarization in AG Dra (Yoo et al 2002). From far-UV spectra obtained with the Hopkins Ultraviolet Telescope (HUT; see Kruk et al 1995), 6 we obtained the intensity ratio IðLyÞ=IðO viÞ 1=1000.…”
Section: Discussionmentioning
confidence: 99%